2019
DOI: 10.1111/echo.14373
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of left ventricular myocardial strain by four‐dimensional speckle tracking echocardiography combined with red cell distribution width in heart failure with preserved ejection fraction

Abstract: Objectives The diagnostic difficulty of heart failure with preserved ejection fraction (HFpEF) is differentiating it in patients with similar symptoms and signs. This study aimed to assess the potential predictive value of left ventricular global longitudinal strain (GLS), global radial strain (GRS), global circumferential strain (GCS), and global area strain (GAS) measured by four‐dimensional speckle tracking echocardiography (4DSTE) combined with red cell distribution width (RDW) in patients with HFpEF. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…GAS reflects a change in the endocardial surface from its original dimensions at the end of diastole. Previous studies have shown that GAS is a reproducible index for detecting early systolic dysfunction, with high sensitivity and better feasibility than other myocardial deformation measurements 15,26 . GAS was higher in BD patients with than without fQRS+.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…GAS reflects a change in the endocardial surface from its original dimensions at the end of diastole. Previous studies have shown that GAS is a reproducible index for detecting early systolic dysfunction, with high sensitivity and better feasibility than other myocardial deformation measurements 15,26 . GAS was higher in BD patients with than without fQRS+.…”
Section: Discussionmentioning
confidence: 84%
“…Compared with 2D echocardiography, 4D STE has many advantages. Multidirectional heart movements may result in missing traces when using 2D STE, 13 whereas 4D STE offers a 3D view of the heart enabling to follow stress changes in each part of the LV using real‐time color mapping 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Diastolic dysfunction was exclusively studied by Mitter et al who came up with their publication "A Test in Context E/A and E/e/ to Assess Diastolic Dysfunction and LV Filling Pressure." 19 [20][21][22][23] In our study Echocardiography and Doppler was performed on every patient, and Diastolic dysfunction studied using E/A ratio as a marker of LV function. LVEF left ventricular ejection fraction was derived by LVEF: (SV/EDV)×100.…”
Section: Resultsmentioning
confidence: 99%
“…Strain is defined as a percentage change of myocardial length or thickness from the original value. STE is a reliable method for evaluating systolic function in patients with various diseases 8,9,11 . In previous studies, subclinical LV systolic dysfunction in SS patients was demonstrated by conventional echo parameters 10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, LV function in SS patients was evaluated with standard 2D Doppler echocardiographic parameters 10 . In recent years, 4DSTE was introduced as a more reliable and sensitive test to evaluate subclinical LV function in patients with various clinical disorders 9,11 …”
Section: Introductionmentioning
confidence: 99%